KEBIJAKAN PENATAAN PEDAGANG KAKI LIMA PASAR TIBAN JALAN LINGKAR SALATIGA - Trianggono, Bagus (KRITIS, 2019)
The Salatiga Ring Road (JLS) was built with the aim of breaking down congestion on the Salatiga City protocol road. However, since 2011 there has been an anomaly in the JLS section where there has been trading activity (tiban market) every Sunday. The existence of the JLS tiban market clearly violates many existing regulations. Therefore, this paper intends to investigate the process of the emergence of the tiban market, then the position of the tiban market in the context of public policy and the implementation of policy products (Mayor's discretion) in structuring the tiban market street vendors. This research uses a qualitative approach and descriptive explanatory research type. The results showed that the tiban market emerged on the initiative of the local community who saw the economic potential on these roads. Furthermore, at the formal legal level the tiban market does not yet have permanent legal force, and for now it is still using the mayor's discretion from the 2014 hearing. So that discretion is used as the basis for structuring the street vendors (PKL) in the tiban market. The institution in charge of overseeing the management of street vendors is the Civil Service Police Unit (Satpol PP) and is assisted by the PKL association.